A survey on the reading preferences of Miriam High School Students - Letargo, Ma. Katrina Joy R. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1993)
This study analyzed the reading preferences of 242 Miriam High School students. Using a questionnaire, it examined the reading preferences of family members and students on books, magazines, newspapers, and comics. Findings of the study revealed that reading materials preferred by parents/family members are similar with those preferred by the student respondents and that most reading materials borrowed from the library are fiction books.
Most fiction books read are love/romance stories while non-fiction books read are those that deal with science and english and are frequently needed during the middle of the sem, before exams and when term papers are due. Magazines read are those general in nature and comics preferred are those which are funny/humorous.
Good reading habits should start at home and the school library and teachers should work hand in hand to stimulate and develop the reading interest of each student.
Typescript.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: High school students -- Books and reading -- Philippines -- Quezon City; Reading interests -- Philippines -- Quezon City